Phytochemical Profiles and Cytotoxicity Activities of Eucalyptus Leaf Oils from Eucalyptus Clones - Rita Kartika Sari; Yanico Hadi Prayogo; Agus Purwoko; Anne Carolina; Elisa Ganda Togu Manurung; Gunawan Pasaribu (Jurnal Sylva Lestari, 2026)
Although widely cultivated for wood production in Indonesia, studies on Eucalyptus leaf essential oils (ELEOs) from Eucalyptus clones remain limited. This study investigated the yield, phytochemical profiles, cytotoxic activities, and putative compounds associated with the cytotoxicity of ELEOs obtained from seven Eucalyptus clones cultivated in North Sumatra, Indonesia. The oils were extracted by water-and-steam distillation for 1.5 h, starting when the first oil droplet appeared. Phytochemical profiles were characterized by gas chromatography-mass spectrometry, and cytotoxicity against A549 lung cancer and B16-F10 murine melanoma cells was evaluated in vitro. Multivariate analyses, such as orthogonal partial least squares and principal component analysis, together with molecular docking, were used to identify compounds associated with cytotoxicity. Essential oil yield ranged from 0.15% to 0.39% (w/w), while eucalyptol, the principal quality marker of ELEO, ranged from 7.98% to 41.69% among the clones. The clone of Eucalyptus grandis x Eucalyptus open-pollinated clone (GOP) exhibited the lowest IC50 value for B16-F10 cells (165.3 microgram/mL), and the clone of E. urophylla x Eucalyptus open-pollinated clone (UOP1) exhibited the lowest IC50 value for A549 cells (111.9 microgram/mL). According to multivariate analyses and molecular docking, alpha-pinene, (-)-spathulenol, and (-)-globulol are compounds that likely exhibit cytotoxicity against B16-F10 cells, while gamma-terpinene, o-cymene, o-cymen-5-ol, and leptospermone are compounds that likely exhibit cytotoxicity against A549 cells. However, in normal cell lines, it was not possible to achieve cytotoxic selectivity, as the biological significance of the observed cytotoxic responses is not yet established. In general, the results indicated that the yield, phytochemical composition, and cytotoxic activity of ELEOs derived from Eucalyptus clones depend on the genetic background. Keywords: A549 lung cancer cell lines, B16-F10 murine melanoma cell lines, Gas Chromatography-Mass Spectrometry, molecular docking, multivariate analysis